Peningkatan Kualitas dan Kemasan pada Kelompok Usaha Kerupuk Ikan di Desa Bendar Kecamatan Juwana Kabupaten Pati - Dina Prasetyowati; Rasiman Rasiman; Ipah Budi Minarti; David Firna Setiawan (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2020)
Bendar Village is known as a Fisherman Village because the majority of the population of Bendar Village are fishermen with a total of 55.7% or 880 people. The root of the problem faced by Bendar Village, Juwana District, Pati Regency is the large number of fish catches by fishermen and human resources that have not been maximally empowered, so that they have not been able to improve the welfare of the community both as groups and individually in Bendar Village. Partners in this service are Mina Melati's Joint Business Group (KUB). In running its business, KUB Kerupuk Ikan Mina Melati still applies traditional management. The lack of knowledge of the members of the Mina Melati Fish Crackers KUB is one of the reasons, especially in terms of good cracker production and processing and business management. The activities carried out by this service were Seminar on Procedures for Obtaining PIRT and Proper Hygiene Certification, Lab Testing of Cracker Food Content, PIRT Licensing for Mina Melati Fish Crack KUB, Cracker Packaging Label Design Training, Packaging Training. With this service program, it is hoped that KUB Mina Melati can produce fish crackers that are hygienic and have a high selling value. If the selling value of the results of fish cracker processing is high, the income of the residents will increase, and in turn will have an impact on improving the welfare of the Bendar Village community and making Bendar Village a Fish Crackers Center.